Development and Evaluation of a Novel and Rapid Detection Assay for Botrytis cinerea Based on Loop-Mediated Isothermal Amplification - Duan, Ya-Bing; Ge, Chang-Yan; Zhang, Xiao-Ke; Wang, Jian-Xin; Zhou, Ming-Guo (PLOS ONE, 2014)
Botrytis cinerea is a devastating plant pathogen that causes grey mould disease. In this study, we developed a visual detection method of B. cinerea based on the Bcos5 sequence using loop-mediated isothermal amplification (LAMP) with hydroxynaphthol blue dye (HNB). The LAMP reaction was optimal at 63°C for 45 min. When HNB was added prior to amplification, samples with B. cinerea DNA developed a characteristic sky blue color after the reaction but those without DNA or with DNA of other plant pathogenic fungi did not. Results of HNB staining method were reconfirmed when LAMP products were subjected to gel electrophoresis. The detection limit of this LAMP assay for B. cinerea was 10−3 ng µL−1 of genomic DNA per reaction, which was 10-fold more sensitive than conventional PCR (10−2 ng µL−1). Detection of the LAMP assay for inoculum of B. cinerea was possible in the inoculated tomato and strawberry petals. In the 191 diseased samples, 180 (94.2%) were confirmed as positive by LAMP, 172 (90.1%) positive by the tissue separation, while 147 (77.0%) positive by PCR. Because the LAMP assay performed well in aspects of sensitivity, specificity, repeatability, reliability, and visibility, it is suitable for rapid detection of B. cinerea in infected plant materials prior to storage and during transportation, such as cut flowers, fruits and vegetables.